Strategi Peningkatan Kompetensi Pedagogik Guru Untuk Meningkatkan Mutu Sekolah - Tyagita, Brigitta Putri Atika; Iriani, Ade (Universitas Kristen Satya Wacana, 2018)
This study aimed to obtain a strategy to increase the pedagogic competence of teacher to improve school quality. Teacher pedagogy competencies are important to have so that the teacher can understand and direct students to learn well and appropriately, and can help students to actualize their potential. Pedagogy competence of teachers can improve the school quality because one of them seen from a professional teacher and good performance. The subject of this study: 1 principal, 1 vice principal, 6 teachers. The research data was taken through an interview, observation, and document study with source triangulation. Data analysis using SWOT to analyze internal and external factors. The results of the SWOT analysis shows that schools are in the SO or strength-opportunity quadrant, which supports aggressive strategies by utilizing the strengths and opportunities that schools have to improve teacher pedagogic competence. By optimizing the strength factor and the school opportunity, there are 6 strategic plans to increase the pedagogic competence of teachers by emphasizing cooperation among teachers, students and also parents. The strategic plan is to optimize the performance of leaders, optimize collaboration among teachers, the collaboration between teachers and students, optimize external support, optimize teacher pedagogical development, and improve teacher, student, and parent collaboration.